2019
DOI: 10.1097/md.0000000000015523
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extracorporeal shock wave therapy on the treatment of moderate to severe knee osteoarthritis and cartilage lesion

Abstract: Background: Knee osteoarthritis (KOA) is a major cause leading to chronic bone and muscle pain. Extracorporeal shock wave therapy (ESWT) has been applied in treating KOA in recent years. Methods: From April 2016 to April 2017, 82 patients were diagnosed with KOA that received ESWT were selected as the ESWT group. The treatment parameters were as follows, 2.0 bar, 0.25 mJ/mm 2 , and 8 Hz/s for twice a week for 4 weeks continuously. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…In this study, compared with before treatment, after 5 weeks of treatment, the VAS score, WOMAC score, and Lequesne index score of the RE group and NRE group were significantly decreased, while ROM score and JOA score were significantly increased. The results of this study are similar to those of previous reports, and indicate that ESWT can reduce the clinical symptoms of KOA patients and improve knee joint function and quality of life of patients [ 28 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, compared with before treatment, after 5 weeks of treatment, the VAS score, WOMAC score, and Lequesne index score of the RE group and NRE group were significantly decreased, while ROM score and JOA score were significantly increased. The results of this study are similar to those of previous reports, and indicate that ESWT can reduce the clinical symptoms of KOA patients and improve knee joint function and quality of life of patients [ 28 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Wang C. et al observed improved tissue distributions, including cortical bone, cancellous bone, and fibrous tissue, in many studies using extracorporeal shockwaves to the subchondral bone of the medium tibia condyle. ESWT increased BMP-2 and osteocalcin expression in OA rats, which is usually linked with cell proliferation and extracellular matrix synthesis in healthy osteoblasts [66]. The immunohistochemical examination revealed that the expression of Dickkopf-related protein 1 (DKK-1)-a regulator of osteoblast activity-was considerably greater in OA and significantly decreased after ESWT therapy; these findings show that shock wave stimulation can boost subchondral bone anabolism and improve trabecular microarchitecture.…”
Section: Eswtmentioning
confidence: 82%
“…ere are many current physical treatments, such as electromagnetic therapy [28], acupuncture [29], ultrasound [30], massage [31], spa [32], cupping [33], yoga [34], and laser [35], but there are great differences in the treatment effect on different individuals, and their effect is to relax tense muscles, promote local blood circulation, improve function of the knee joint, and promote absorption and discharge of inflammatory substances.…”
Section: Physical Erapymentioning
confidence: 99%